Experimental Study of Drug Delivery system for Prednisolone Loaded and Released by Mesoporous Silica MCM-41 - Albayati, Talib M.; Jassam, Abd Alkadir A. (Al-Khwarizmi Engineering Journal, 2019)
In the present study, nanoporous material type MCM-41 was prepared by the sol-gel technique and was used as a carrier for prednisolone (PRD) drug delivery. The structural properties of mesoporous were fully characterized by X-ray diffraction (XRD), N2 adsorption /desorption and Fourier-transform infrared (FTIR). The mass transfer in term of adsorption process (loading) and desorption process (releasing) properties were investigated. The maximum drug loading efficiency was equal to 38% and 47.5% at different concentrations. The PRD released was prudently studied in water media of pH 6.8 simulated body fluid (SBF) in according to "United State Pharmacopeia (USP38)". The results proved that the release of prednisolone from MCM-41 was (69.4%) after 24 hr. The data of the released PRD was found to be submitted to a Korsmeyer–Peppas model.